Difference Risk Incident Stunting Based On Age And Gender In Jagran, Tembarak, Temanggung - Mahardika Ratih Resti Andani; Este Latifahanun (Jurnal EduHealth, 2024)
Stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their body length or height being below standard (WHO 2015). Indonesia is currently having a problem with stunting. The results of the 2013 Basic Health Research (Riskedas) showed that the prevalence of stunting reached 37.2%. Based on the results of the Indonesian Nutrition Status Survey (SSGI) in 2024, stunting cases in Temanggung Regency will still be at 25.1 percent. With the still high stunting rate, various efforts have been made by the Temanggung Regency Government. This research aims to determine difference risk incident stunting based on age and gender in jagran, tembarak, temanggung. Cross-sectional results show that the p-value of the group age with depression term short of 0.000. Results chi-square analysis type sex with incident stunting with mark p-value as big as 0.002.